2013
DOI: 10.1038/nsmb.2550
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mus81–Eme1 Holliday junction resolvase in response to DNA damage

Abstract: Structure-specific DNA endonucleases have critical roles during DNA replication, repair and recombination, yet they also harbor the potential for causing genome instability. Controlling these enzymes may be essential to ensure efficient processing of ad hoc substrates and to prevent random, unscheduled processing of other DNA structures, but it is unknown whether structure-specific endonucleases are regulated in response to DNA damage. Here, we uncover DNA damage-induced activation of Mus81-Eme1 Holliday junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 37 publications
(38 reference statements)
8
84
0
Order By: Relevance
“…These results indicate that the absence of Sgs1 or Yen1 does not cause changes in the dynamics of activation of this endonuclease, even in the presence of DNA damage during chromosome replication. Moreover, these data also show that the hyperphosphorylation of Mms4 does not increase in budding yeast cells lacking Sgs1 with respect to SGS1 + cells (compare Figures 4A and 5A), unlike Eme1 Mms4 phosphorylation in S. pombe (46). Mms4 phosphorylation does not increase either in the absence of both Sgs1 and Yen1 (compare Figures 4A and 5B).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…These results indicate that the absence of Sgs1 or Yen1 does not cause changes in the dynamics of activation of this endonuclease, even in the presence of DNA damage during chromosome replication. Moreover, these data also show that the hyperphosphorylation of Mms4 does not increase in budding yeast cells lacking Sgs1 with respect to SGS1 + cells (compare Figures 4A and 5A), unlike Eme1 Mms4 phosphorylation in S. pombe (46). Mms4 phosphorylation does not increase either in the absence of both Sgs1 and Yen1 (compare Figures 4A and 5B).…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, the regulation of Mus81-Mms4 through Mms4 phosphorylation is independent of the presence of DNA damage during chromosome replication, even if the number of DNA lesions could accumulate due to pathological situations originated by the absence of proteins with which it has overlapping functions. A recent work has shown that, in S. pombe , Eme1 Mms4 phosphorylation is increased in G2 by damage induced by camptothecin or bleomycin, which is accompanied by enhanced activity of Mus81-Eme1 (46). However, our work indicates that MMS does not induce or modify the phosphorylation of budding yeast Mms4 and therefore the activity of Mus81-Mms4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations